Health and Beauty : A Book for Girls - Foley, Elizabeth; Cocker, Edith A. (London : The Health & Cleanliness Council)
1939-10 1939 1930s 27 pages ; illustrations A CLEAN INSIDE Our digestive tract is thirty feet long, beginning at the mouth and ending, after many twists and turns, at the large intestine or colon. If this long tube is unclean our general health will suffer in ways innumerable, and, what is more, the appearance of the outside of the body will reflect the unhealthy state within. When the drains of a house become choked up by neglect, the whole house becomes unwholesome from the effects of poisonous gases that arise from the decomposing waste. In like manner our intestines may become a foul cesspool, where body wastes decompose and poison the body through the channels of the blood. Every time we eat, a process of digestion is set up, the body taking what it requires to build up blood and bone, muscles and fat, and to provide us with heat and energy. What it does not require and what it cannot use is waste, and must be passed out of the body regularly if the body is to be clean and healthy. It is largely what we eat and how we eat that determines the proper action of "the inside," and this is a matter largely under our own control. We eat too quickly, quite forgetting that our mouth is a miniature mill that not only grinds but mixes the food with a digestive fluid in order to prepare it for proper digestion lower down. This mastication is absolutely under our control; yet what a lot of people bolt their food. Girls are terrible sinners in this respect! Choose well, chew well, and you will be well. Then there is the vexed question of drink — no drink at meals, no drink between meals — which is right? Some people are benefited by taking little or no fluid during a meal, and certainly the washing down of food by quantities of fluid is condemned by doctors. The flow of saliva from the glands in the mouth has work to do. Saliva keeps the teeth clean and starts the digestion [illustration] Choose well, chew well and you will BE well. 21 177/5/8/4